Nota editorial / Edición 2015, v. 13, n. 1 (enero / diciembre) - Leite, Marcos Esdras; Pereira , Luiz Andrei Gonçalves (Revista Cerrados, 2016)
Nota editorial / Edición 2015, v. 13, n. 1 (enero / diciembre)